Defective neuroepithelial cell cohesion affects tangential branchiomotor neuron migration in the zebrafish neural tube - Stockinger, Petra; Heisenberg, Carl-Philipp J; Maître, Jean-Léon (Development)
Facial branchiomotor neurons (FBMNs) in zebrafish and mouse embryonic hindbrain undergo a characteristic tangential migration from rhombomere (r) 4, where they are born, to r6/7. Cohesion among neuroepithelial cells (NCs) has been suggested to function in FBMN migration by inhibiting FBMNs positioned in the basal neuroepithelium such that they move apically between NCs towards the midline of the neuroepithelium instead of tangentially along the basal side of the neuroepithelium towards r6/7. However, direct experimental evaluation of this hypothesis is still lacking. Here, we have used a combination of biophysical cell adhesion measurements and high-resolution time-lapse microscopy to determine the role of NC cohesion in FBMN migration. We show that reducing NC cohesion by interfering with Cadherin 2 (Cdh2) activity results in FBMNs positioned at the basal side of the neuroepithelium moving apically towards the neural tube midline instead of tangentially towards r6/7. In embryos with strongly reduced NC cohesion, ectopic apical FBMN movement frequently results in fusion of the bilateral FBMN clusters over the apical midline of the neural tube. By contrast, reducing cohesion among FBMNs by interfering with Contactin 2 (Cntn2) expression in these cells has little effect on apical FBMN movement, but reduces the fusion of the bilateral FBMN clusters in embryos with strongly diminished NC cohesion. These data provide direct experimental evidence that NC cohesion functions in tangential FBMN migration by restricting their apical movement.

The role of adhesion energy in controlling cell-cell contacts - Maître, Jean-Léon; Heisenberg, Carl-Philipp J (Current Opinion in Cell Biology)
Recent advances in microscopy techniques and biophysical measurements have provided novel insight into the molecular, cellular and biophysical basis of cell adhesion. However, comparably little is known about a core element of cell–cell adhesion—the energy of adhesion at the cell–cell contact. In this review, we discuss approaches to understand the nature and regulation of adhesion energy, and propose strategies to determine adhesion energy between cells in vitro and in vivo.

Competition and opportunity shape the reproductive tactics of males in the ant Cardiocondyla obscurior - Cremer, Sylvia; Schrempf, Alexandra; Heinze, Jürgen (PLoS One)
Context-dependent adjustment of mating tactics can drastically increase the mating success of behaviourally flexible animals. We used the ant Cardiocondyla obscurior as a model system to study adaptive adjustment of male mating tactics. This species shows a male diphenism of wingless fighter males and peaceful winged males. Whereas the wingless males stay and exclusively mate in the maternal colony, the mating behaviour of winged males is plastic. They copulate with female sexuals in their natal nests early in life but later disperse in search for sexuals outside. In this study, we observed the nest-leaving behaviour of winged males under different conditions and found that they adaptively adjust the timing of their dispersal to the availability of mating partners, as well as the presence, and even the type of competitors in their natal nests. In colonies with virgin female queens winged males stayed longest when they were the only male in the nest. They left earlier when mating partners were not available or when other males were present. In the presence of wingless, locally mating fighter males, winged males dispersed earlier than in the presence of docile, winged competitors. This suggests that C. obscurior males are capable of estimating their local breeding chances and adaptively adjust their dispersal behaviour in both an opportunistic and a risk-sensitive way, thus showing hitherto unknown behavioural plasticity in social insect males.

The formation of the Bicoid morphogen gradient requires protein movement from anteriorly localized source - Little, Shawn; Tkacik, Gasper; Kneeland, Thomas; Wieschaus, Eric; Gregor, Thomas (PLoS Biology)
The Bicoid morphogen gradient directs the patterning of cell fates along the anterior-posterior axis of the syncytial Drosophila embryo and serves as a paradigm of morphogen-mediated patterning. The simplest models of gradient formation rely on constant protein synthesis and diffusion from anteriorly localized source mRNA, coupled with uniform protein degradation. However, currently such models cannot account for all known gradient characteristics. Recent work has proposed that bicoid mRNA spatial distribution is sufficient to produce the observed protein gradient, minimizing the role of protein transport. Here, we adapt a novel method of fluorescent in situ hybridization to quantify the global spatio-temporal dynamics of bicoid mRNA particles. We determine that >90% of all bicoid mRNA is continuously present within the anterior 20% of the embryo. bicoid mRNA distribution along the body axis remains nearly unchanged despite dynamic mRNA translocation from the embryo core to the cortex. To evaluate the impact of mRNA distribution on protein gradient dynamics, we provide detailed quantitative measurements of nuclear Bicoid levels during the formation of the protein gradient. We find that gradient establishment begins 45 minutes after fertilization and that the gradient requires about 50 minutes to reach peak levels. In numerical simulations of gradient formation, we find that incorporating the actual bicoid mRNA distribution yields a closer prediction of the observed protein dynamics compared to modeling protein production from a point source at the anterior pole. We conclude that the spatial distribution of bicoid mRNA contributes to, but cannot account for, protein gradient formation, and therefore that protein movement, either active or passive, is required for gradient formation.

Modern ionotropic glutamate receptor with a K+ selectivity signature sequence - Janovjak, Harald L; Sandoz, Guillaume; Isacoff, Ehud (Nature Communications)
Glutamate is the major excitatory neurotransmitter in the mammalian central nervous system and gates non-selective cation channels. The origins of glutamate receptors are not well understood as they differ structurally and functionally from simple bacterial ligand-gated ion channels. Here we report the discovery of an ionotropic glutamate receptor that combines the typical eukaryotic domain architecture with the 'TXVGYG' signature sequence of the selectivity filter found in K+ channels. This receptor exhibits functional properties intermediate between bacterial and eukaryotic glutamate-gated ion channels, suggesting a link in the evolution of ionotropic glutamate receptors.

Morphology evolution of Cu2−xS nanoparticles: from spheres to dodecahedrons - Li, Wenhua; Shavel, Alexey; Guzman, Roger; Rubio Garcia, Javier; Flox, Cristina; Fan, Jiandong; Cadavid, Doris; Ibáñez, Maria; Arbiol, Jordi; Morante, Joan; Cabot, Andreu (Chemical Communications)
An oriented attachment and growth mechanism allows an accurate control of the size and morphology of Cu2-xS nanocrystals, from spheres and disks to tetradecahedrons and dodecahedrons. The synthesis conditions and the growth mechanism are detailed here.

Arithmetic harmonic analysis on character and quiver varieties - Tamas Hausel; Letellier, Emmanuel; Rodríguez Villegas, Fernando (Duke Mathematical Journal)
We propose a general conjecture for the mixed Hodge polynomial of the generic character varieties of representations of the fundamental group of a Riemann surface of genus g to GLn(C) with fixed generic semisimple conjugacy classes at k punctures. This conjecture generalizes the Cauchy identity for Macdonald polynomials and is a common generalization of two formulas that we prove in this paper. The first is a formula for the E-polynomial of these character varieties which we obtain using the character table of GLn(Fq). We use this formula to compute the Euler characteristic of character varieties. The second formula gives the Poincaré polynomial of certain associated quiver varieties which we obtain using the character table of gln(Fq). In the last main result we prove that the Poincaré polynomials of the quiver varieties equal certain multiplicities in the tensor product of irreducible characters of GLn(Fq). As a consequence we find a curious connection between Kac-Moody algebras associated with comet-shaped, and typically wild, quivers and the representation theory of GLn(Fq).

Multimode mediated qubit-qubit coupling and dark-state symmetries in circuit quantum electrodynamics - Filipp, Stefan; Göppl, M; Johannes Fink; Baur, Matthias P; Bianchetti, R; Steffen, L. Kraig; Wallraff, Andreas (Physical Review A - Atomic, Molecular, and Optical Physics)
Microwave cavities with high quality factors enable coherent coupling of distant quantum systems. Virtual photons lead to a transverse interaction between qubits when they are nonresonant with the cavity but resonant with each other. We experimentally investigate the inverse scaling of the interqubit coupling with the detuning from a cavity mode and its proportionality to the qubit-cavity interaction strength. We demonstrate that the enhanced coupling at higher frequencies is mediated by multiple higher-harmonic cavity modes. Moreover, we observe dark states of the coupled qubit-qubit system and analyze their relation to the symmetry of the applied driving field at different frequencies.

Adaptive response and enlargement of dynamic range - Tamar Friedlander; Brenner, Naama (Mathematical Biosciences and Engineering)
Many membrane channels and receptors exhibit adaptive, or desensitized, response to a strong sustained input stimulus, often supported by protein activity-dependent inactivation. Adaptive response is thought to be related to various cellular functions such as homeostasis and enlargement of dynamic range by background compensation. Here we study the quantitative relation between adaptive response and background compensation within a modeling framework. We show that any particular type of adaptive response is neither sufficient nor necessary for adaptive enlargement of dynamic range. In particular a precise adaptive response, where system activity is maintained at a constant level at steady state, does not ensure a large dynamic range neither in input signal nor in system output. A general mechanism for input dynamic range enlargement can come about from the activity-dependent modulation of protein responsiveness by multiple biochemical modification, regardless of the type of adaptive response it induces. Therefore hierarchical biochemical processes such as methylation and phosphorylation are natural candidates to induce this property in signaling systems.

The number of equilibria in the diallelic Levene model with multiple demes - Sebastian Novak (Theoretical Population Biology)
The Levene model is the simplest mathematical model to describe the evolution of gene frequencies in spatially subdivided populations. It provides insight into how locally varying selection promotes a population’s genetic diversity. Despite its simplicity, interesting problems have remained unsolved even in the diallelic case. In this paper we answer an open problem by establishing that for two alleles at one locus and J demes, up to 2J−1 polymorphic equilibria may coexist. We first present a proof for the case of stable monomorphisms and then show that the result also holds for protected alleles. These findings allow us to prove that any odd number (up to 2J−1) of equilibria is possible, before we extend the proof to even numbers. We conclude with some numerical results and show that for J>2, the proportion of parameter space affording this maximum is extremely small.

Internal structure of the fly elementary motion detector - Eichner, Hubert; Maximilian Jösch; Schnell, Bettina; Reiff, Dierk F; Borst, Alexander (Neuron)
Recent experiments have shown that motion detection in Drosophila starts with splitting the visual input into two parallel channels encoding brightness increments (ON) or decrements (OFF). This suggests the existence of either two (ON-ON, OFF-OFF) or four (for all pairwise interactions) separate motion detectors. To decide between these possibilities, we stimulated flies using sequences of ON and OFF brightness pulses while recording from motion-sensitive tangential cells. We found direction-selective responses to sequences of same sign (ON-ON, OFF-OFF), but not of opposite sign (ON-OFF, OFF-ON), refuting the existence of four separate detectors. Based on further measurements, we propose a model that reproduces a variety of additional experimental data sets, including ones that were previously interpreted as support for four separate detectors. Our experiments and the derived model mark an important step in guiding further dissection of the fly motion detection circuit.

Min protein patterns emerge from rapid rebinding and membrane interaction of MinE - Martin Loose; Fischer-Friedrich, Elisabeth; Herold, Christoph; Kruse, Karsten; Schwille, Petra (Nature Structural and Molecular Biology)
In Escherichia coli, the pole-to-pole oscillation of the Min proteins directs septum formation to midcell, which is required for symmetric cell division. In vitro, protein waves emerge from the self-organization of MinD, a membrane-binding ATPase, and its activator MinE. For wave propagation, the proteins need to cycle through states of collective membrane binding and unbinding. Although MinD presumably undergoes cooperative membrane attachment, it is unclear how synchronous detachment is coordinated. We used confocal and single-molecule microscopy to elucidate the order of events during Min wave propagation. We propose that protein detachment at the rear of the wave, and the formation of the E-ring, are accomplished by two complementary processes: first, local accumulation of MinE due to rapid rebinding, leading to dynamic instability; and second, a structural change induced by membrane-interaction of MinE in an equimolar MinD-MinE (MinDE) complex, which supports the robustness of pattern formation.

Protein self-organization: Lessons from the min system - Martin Loose; Kruse, Karsten; Schwille, Petra (Annual Review of Biophysics)
One of the most fundamental features of biological systems is probably their ability to self-organize in space and time on different scales. Despite many elaborate theoretical models of how molecular self-organization can come about, only a few experimental systems of biological origin have so far been rigorously described, due mostly to their inherent complexity. The most promising strategy of modern biophysics is thus to identify minimal biological systems showing self-organized emergent behavior. One of the best-understood examples of protein self-organization, which has recently been successfully reconstituted in vitro, is represented by the oscillations of the Min proteins in Escherichia coli. In this review, we summarize the current understanding of the mechanism of Min protein self-organization in vivo and in vitro. We discuss the potential of the Min oscillations to sense the geometry of the cell and suggest that spontaneous protein waves could be a general means of intracellular organization. We hypothesize that cooperative membrane binding and unbinding, e.g., as an energy-dependent switch, may act as an important regulatory mechanism for protein oscillations and pattern formation in the cell.

Lack of global dosage compensation in Schistosoma mansoni, a female-heterogametic parasite - Vicoso, Beatriz; Bachtrog, Doris (Genome Biology and Evolution)
Many species have morphologically and genetically differentiated sex chromosomes, such as the XY pair of mammals. Y chromosomes are often highly degenerated and carry few functional genes, so that XY males have only one copy of most Xlinked genes (whereas females have two). As a result, chromosome-wide mechanisms of dosage compensation, such as the mammalian X-inactivation, often evolve to reestablish expression balance. A similar phenomenon is expected in femaleheterogametic species, where ZW females should suffer from imbalances due to W-chromosome degeneration. However, no global dosage compensation mechanisms have been detected in the two independent ZW systems that have been studied systematically (birds and silkworm), leading to the suggestion that lack of global dosage compensation may be a general feature of female-heterogametic species. However, analyses of other independently evolved ZW systems are required to test if this is the case. In this study, we use published genomic and expression data to test for the presence of global dosage compensation in Schistosoma mansoni, a trematode parasite that causes schistosomiasis in humans. We find that Z-linked expression is reduced relative to autosomal expression in females but not males, consistent with incomplete or localized dosage compensation. This gives further support to the theory that female-heterogametic species may not require global mechanisms of dosage compensation.

Structure of the membrane domain of respiratory complex i - Efremov, Rouslan G; Leonid Sazanov (Nature)
Complex I is the first and largest enzyme of the respiratory chain, coupling electron transfer between NADH and ubiquinone to the translocation of four protons across the membrane. It has a central role in cellular energy production and has been implicated in many human neurodegenerative diseases. The L-shaped enzyme consists of hydrophilic and membrane domains. Previously, we determined the structure of the hydrophilic domain. Here we report the crystal structure of the Esherichia coli complex I membrane domain at 3.0 Ã. resolution. It includes six subunits, NuoL, NuoM, NuoN, NuoA, NuoJ and NuoK, with 55 transmembrane helices. The fold of the homologous antiporter-like subunits L, M and N is novel, with two inverted structural repeats of five transmembrane helices arranged, unusually, face-to-back. Each repeat includes a discontinuous transmembrane helix and forms half of a channel across the membrane. A network of conserved polar residues connects the two half-channels, completing the proton translocation pathway. Unexpectedly, lysines rather than carboxylate residues act as the main elements of the proton pump in these subunits. The fourth probable proton-translocation channel is at the interface of subunits N, K, J and A. The structure indicates that proton translocation in complex I, uniquely, involves coordinated conformational changes in six symmetrical structural elements.

Respiratory complex I: 'steam engine' of the cell? - Efremov, Rouslan G; Leonid Sazanov (Current Opinion in Structural Biology)
Complex I is the first enzyme of the respiratory chain and plays a central role in cellular energy production. It has been implicated in many human neurodegenerative diseases, as well as in ageing. One of the biggest membrane protein complexes, it is an L-shaped assembly consisting of hydrophilic and membrane domains. Previously, we have determined structures of the hydrophilic domain in several redox states. Last year was marked by fascinating breakthroughs in the understanding of the complete structure. We described the architecture of the membrane domain and of the entire bacterial complex I. X-ray analysis of the larger mitochondrial enzyme has also been published. The core subunits of the bacterial and mitochondrial enzymes have remarkably similar structures. The proposed mechanism of coupling between electron transfer and proton translocation involves long-range conformational changes, coordinated in part by a long α-helix, akin to the coupling rod of a steam engine.

Evolution of respiratory complex I "Supernumerary" subunits are present in the α-proteobacterial enzyme - Yip, Chui Y; Harbour, Michael E; Jayawardena, Kamburapola G; Fearnley, Ian M; Leonid Sazanov (Journal of Biological Chemistry)
Modern α-proteobacteria are thought to be closely related to the ancient symbiont of eukaryotes, an ancestor of mitochondria. Respiratory complex I from α-proteobacteria and mitochondria is well conserved at the level of the 14 "core" subunits, consistent with that notion. Mitochondrial complex I contains the core subunits, present in all species, and up to 31 "supernumerary" subunits, generally thought to have originated only within eukaryotic lineages. However, the full protein composition of an α-proteobacterial complex I has not been established previously. Here, we report the first purification and characterization of complex I from the α-proteobacterium Paracoccus denitrificans. Single particle electron microscopy shows that the complex has a well defined L-shape. Unexpectedly, in addition to the 14 core subunits, the enzyme also contains homologues of three supernumerary mitochondrial subunits as follows: B17.2, AQDQ/18, and 13 kDa (bovine nomenclature). This finding suggests that evolution of complex I via addition of supernumerary or "accessory" subunits started before the original endosymbiotic event that led to the creation of the eukaryotic cell. It also provides further confirmation that α-proteobacteria are the closest extant relatives of mitochondria.

Spatio-temporal extraction of articulated models in a graph pyramid - Artner, Nicole M.; Ion, Adrian; Kropatsch, Walter G. (Graph-Based Representations in Pattern Recognition)
This paper presents a method to create a model of an articulated object using the planar motion in an initialization video. The model consists of rigid parts connected by points of articulation. The rigid parts are described by the positions of salient feature-points tracked throughout the video. Following a filtering step that identifies points that belong to different objects, rigid parts are found by a grouping process in a graph pyramid. Valid articulation points are selected by verifying multiple hypotheses for each pair of parts.

Droplet and cluster formation in freely falling granular streams - Waitukaitis, Scott R; Grütjen, Helge; Royer, John; Jaeger, Heinrich (Physical Review E)
Particle beams are important tools for probing atomic and molecular interactions. Here we demonstrate that particle beams also offer a unique opportunity to investigate interactions in macroscopic systems, such as granular media. Motivated by recent experiments on streams of grains that exhibit liquid-like breakup into droplets, we use molecular dynamics simulations to investigate the evolution of a dense stream of macroscopic spheres accelerating out of an opening at the bottom of a reservoir. We show how nanoscale details associated with energy dissipation during collisions modify the stream\'s macroscopic behavior. We find that inelastic collisions collimate the stream, while the presence of short-range attractive interactions drives structure formation. Parameterizing the collision dynamics by the coefficient of restitution (i.e., the ratio of relative velocities before and after impact) and the strength of the cohesive interaction, we map out a spectrum of behaviors that ranges from gaslike jets in which all grains drift apart to liquid-like streams that break into large droplets containing hundreds of grains. We also find a new, intermediate regime in which small aggregates form by capture from the gas phase, similar to what can be observed in molecular beams. Our results show that nearly all aspects of stream behavior are closely related to the velocity gradient associated with vertical free fall. Led by this observation, we propose a simple energy balance model to explain the droplet formation process. The qualitative as well as many quantitative features of the simulations and the model compare well with available experimental data and provide a first quantitative measure of the role of attractions in freely cooling granular streams.

Ultracold and dense samples of ground-state molecules in lattice potentials - Nägerl, Hanns; Mark, Manfred; Haller, Elmar; Gustavsson, Mattias; Hart, Russell; Danzl, Johann G (Journal of Physics: Conference Series)
We produce an ultracold and dense sample of rovibronic ground state Cs 2 molecules close to the regime of quantum degeneracy, in a single hyperfine level, in the presence of an optical lattice. The molecules are individually trapped, in the motional ground state of an optical lattice well, with a lifetime of 8 s. For preparation, we start with a zero-temperature atomic Mott-insulator state with optimized double-site occupancy and efficiently associate weakly-bound dimer molecules on a Feshbach resonance. Despite extremely weak Franck-Condon wavefunction overlap, the molecules are subsequently transferred with >50% efficiency to the rovibronic ground state by a stimulated four-photon process. Our results present a crucial step towards the generation of Bose-Einstein condensates of ground-state molecules and, when suitably generalized to polar heteronuclear molecules such as RbCs, the realization of dipolar many-body quantum-gas phases in periodic potentials.